“Another one bites the dust”: war dreams in a long dream series - Schredl, Michael (International journal of dream research, 2024)
Wars have been fought and are still fought in many parts of the world. Based on the continuity hypothesis of dreaming, it is plausible that persons who experienced war also quite often dream about it. However, war-related dreams can also be found in persons who were never directly exposed to war. In a long dream series of 14,064 dreams recorded between 1984 and 2018 by a male dreamer, 0.96% of the dreams included war topics. A very small percentage of war dreams (3.7%) were related to wars that actually happened during that time. Thus, the question remains whether war-related dreams reflect waking-life worries about war or are a dramatized version of personal issues of the dreamer. As an increasing number of studies showing that political issues can be incorporated into dreams, it would be very interesting to study whether and how strong topics like worries associated with climate change or war affect dreams. In this case, dream research can expand the methodology of political psychology.